MCM8IP activates the MCM8-9 helicase to promote DNA synthesis and homologous recombination upon DNA damage - Jen-Wei Huang (Nature Portfolio, 2020)
Homologous recombination (HR) is an essential DNA repair pathway for genomic stability. Here the authors show that C17orf53/MCM8IP, an OB-fold containing protein, promotes HR through direct binding and activation of the MCM8-9 helicase complex.